2010
DOI: 10.1371/journal.pone.0008742
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Infection Specifically Increases the Levels of Key Host MicroRNAs

Abstract: BackgroundThe apicomplexan parasite Toxoplasma gondii can infect and replicate in virtually any nucleated cell in many species of warm-blooded animals; thus, it has evolved the ability to exploit well-conserved biological processes common to its diverse hosts. Here we have investigated whether Toxoplasma modulates the levels of host microRNAs (miRNAs) during infection.Methodology/Principal FindingsUsing microarray profiling and a combination of conventional molecular approaches we report that Toxoplasma specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 40 publications
(61 reference statements)
10
83
0
Order By: Relevance
“…2C), we did not observe the nontemplated primer-extension products in any reaction performed on total RNA. Based on our previous observation that pri-miR-106a-363 is undetectable in uninfected HFFs or in HFFs infected with Toxoplasma (Zeiner et al 2010) and on the results presented in Figure 2D, we conclude that miR-106a-363 is likely not affected by Toxoplasma infection. In contrast, based on our observation that primiR-17-92 is significantly increased in Toxoplasma-infected HFFs and that the mature miR-18 and miR-19 members derived from pri-miR-17-92 are also increased (Zeiner et al 2010), and upon the results of Figure 2D, it appears that a contributor to the rise in miR-17 family levels is miR-17, itself.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…2C), we did not observe the nontemplated primer-extension products in any reaction performed on total RNA. Based on our previous observation that pri-miR-106a-363 is undetectable in uninfected HFFs or in HFFs infected with Toxoplasma (Zeiner et al 2010) and on the results presented in Figure 2D, we conclude that miR-106a-363 is likely not affected by Toxoplasma infection. In contrast, based on our observation that primiR-17-92 is significantly increased in Toxoplasma-infected HFFs and that the mature miR-18 and miR-19 members derived from pri-miR-17-92 are also increased (Zeiner et al 2010), and upon the results of Figure 2D, it appears that a contributor to the rise in miR-17 family levels is miR-17, itself.…”
Section: Resultssupporting
confidence: 66%
“…Previously, we concluded that one or both of these loci are affected by Toxoplasma infection but could not determine which. Although the primary transcript (pri-) for miR-17-92 increased in abundance in Toxoplasmainfected cells, we were unable to detect pri-miR-106a-363 (Zeiner et al 2010), precluding any conclusion on its contribution to the increased levels of mature miR-17 family members; this leaves open the possibilities that pri-miR106a-363 transcription peaks at time points not examined and/or that pri-miR-106a-363 is so rapidly processed into mature miRNAs that it is not present at levels high enough to be detected.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…34,35 The let-7 family is commonly downregulated by infection with several of these parasites, namely Cryptosporidium, 30,31 Plasmodium 32 and Toxoplasma. 33 However, the above studies also suggest that the expression of most miRNAs is altered in a parasite specific manner.…”
Section: Microrna Responses To Pathogenic Bacteriamentioning
confidence: 98%
“…[27][28][29] Several studies have explored the impact of apicomplexan parasites, many of which cause serious diseases in humans, on host microRNA expression during infection. Interestingly, modulation of host microRNA profiles was observed upon infection with several parasites, including Cryptosporidium parvum, 30,31 Plasmodium chabaudii, 32 Toxoplasma gondii 33 and Eimeria papillata. 34,35 The let-7 family is commonly downregulated by infection with several of these parasites, namely Cryptosporidium, 30,31 Plasmodium 32 and Toxoplasma.…”
Section: Microrna Responses To Pathogenic Bacteriamentioning
confidence: 99%